Saul-Wilson Syndrome Missense Allele Does Not Show Obvious Golgi Defects in a C. elegans Model - Zafra, Isabella (MicroPubl Biol, 2021)
Saul-Wilson Syndrome is an ultra-rare skeletal syndrome caused by a mutation in the COG4 gene resulting in a glycine-to-arginine substitution at amino acid position 516. The COG4 gene encodes one of 8 subunits of the conserved oligomeric Golgi complex. Using CRISPR-Cas9, our lab generated a C. elegans model for Saul-Wilson Syndrome by recreating the same glycine-to-arginine substitution in the worm ortholog cogc-4. Upon observation, the cogc-4(av107) worms did not display any obvious differences compared to wild-type worms. We used a variety of assays including stressing the worms using heat and Paraquat, as well as RNAi against the 7 other COG complex subunit genes in an attempt to uncover a phenotype. Our data suggest that this mutation in cogc-4(av107) worms does not lead to a detectable phenotype. Further studies should aim at more directly assessing Golgi function in this disease model.